Response to comments on "A numerical method to determine interdiffusion coefficients of Cu6Sn5 and Cu3Sn intermetallic compounds". (February 2016) - Li, J.F.; Agyakwa, P.A.; Johnson, C.M.
Abstract: Comments have recently been made by Yuan et al. [1] to deny one statement in our paper [2], Eq. (21) in Wagner's paper [3] can be used to accurately calculate the integrated interdiffusion coefficient for an incremental diffusion couple only under the assumption of constant Molar volume for all phases. We respond here to explain how they misunderstood our mathematical deduction, made a mistake in deriving a couple of equations, falsely cited our work and employed unjustifiable assumption. As a result, we believe that their comments are invalid to deny our statement.